PWE-087 Liver biopsy interpretative challenges – a four year tertiary centre review. (22nd June 2015) - Paterson, A; Allison, M; Brais, R; Davies, S
Abstract : Introduction: It is standard UK practice for all patients with a malignant diagnosis to have a multidisciplinary team (MDT) discussion as part of their management which includes a review of any histology. Studies have shown a discrepancy rate of 7–15% between the original and tertiary-centre histopathological diagnoses, although few have explored the impact of such a review for non-malignant pathologies. This study reviewed all liver biopsies referred to our centre, a university teaching hospital, to determine the (a) extent of agreement with the original report; (b) predicted clinical impact of interpretation differences; (c) major diagnostic challenges. Method: All liver biopsies (n = 1333) for lesional and non-lesional assessments referred over four years, 2010–2013, were included. The majority came from ten local hospitals within our regional liver network. Liver resections and referrals for molecular assays only were excluded. The extent of agreement with the original diagnosis and probable impact on clinical management were recorded at the time of the review. A subset was explored in depth to determine more precisely the nature of interpretation differences. Results: The majority of biopsies, 65%, were referred specifically for diagnostic advice; whilst 24% were as part of a transplant assessment or due to transfer of care; and 11% for MDT discussion. In 786 (59%) there was an interpretation difference, 528 (67%) of which were predicted to change management. Cases referred specifically for a diagnostic opinion were more likely to result in predicted management changes than those reviewed prior to an MDT or for other reasons, 45% vs 28% respectively, p < 0.01. In over 70% of cases with architectural/vascular abnormalities, 64% with chronic biliary disease, and just over half where the major pathology was autoimmune hepatitis, (sub)acute hepatitis, or a benign mass lesion, specialist review would have changed management. Although agreement was better for chronic viral hepatitis, fatty liver disease and malignant lesions, in 24–36% of cases altered patient management was predicted post-review. The original and tertiary-centre histopathology reports for 107 biopsies with interpretation differences were reviewed. In 39 (36%) biopsies a definite or differential diagnosis was provided where the referrer had been uncertain; whilst In 38 (35%) cases an alternative diagnosis to the original report was made; and differences in fibrosis or inflammatory activity scoring were present in 25 (23%). The diagnostic challenge involved biliary disease in almost a third, 31%. Conclusion: Non-specialists seek advice appropriately in challenging cases. A specialist pathology review may result in altered management in 40% of cases. Biliary disease is highlighted as a particular diagnostic challenge. Disclosure of interest: None Declared.